Efeitos de diferentes frações inspiradas de oxigênio sobre a dinâmica respiratória em cães submetidos à infusão contínua de propofol e mantidos em ventilação espontânea - Lopes, Patrícia Cristina Ferro [UNESP]; Nunes, Newton [UNESP]; Carareto, Roberta [UNESP]; Nishimori, Celina Tie Duque [UNESP]; de Paula, Danielli Parrilha [UNESP]; Sousa, Marlos Gonçalves [UNESP]; Santos, Paulo Sergio Patto dos [UNESP]; Thiesen, Roberto [UNESP] (My University, 2007)
The effects of several inspired oxygen fractions (FiO 2) on the respiratory dynamics in spontaneously breathing dogs submitted to continuous infusion of propofol were evaluated. Eight adult mongrel dogs were used. Each animal underwent five anesthesias, in each procedure the patient was allowed to breath a different FiO 2, thereby resulting in five groups, namely: G100 (FiO 2 = 1), G80 (FiO 2 = 0.8), G60 (FiO 2 =0.6), G40 (FiO 2 = 0.4), and G20 (FiO 2 = 0.21). To induce anesthesia, propofol was given until the animals allowed orotracheal intubation, followed by immediate continuous infusion of drug. The initial measurement (M0) was recorded thirty minutes after the infusion of propofol has begun. Additional recordings were performed at 15 minute intervals for 60 minutes (M15, M30, M45 and M60). Numeric data were submitted to Analysis of Variance followed by Tukey Test (p<0.05). We recorded significantly lower values of SpO 2 and SaO 2 at G20, whereas PaO 2 varied according to the changes in oxygen. Regarding PaCO 2, the mean of G100 was greater than G20 at M30. However, spontaneously breathing dogs anesthetized with propofol at the rate of 0.7mg/kg/min should not be provided with 100%, 80%, and 21% oxygen owing to the significant compromise of respiratory system.
Effects of several inspired oxygen fractions on the respiratory dynamics in spontaneously breathing dogs undergoing continuous infusion of propofol
Keywords: Dog; Oxygen inspired fraction; Propofol; Respiratory parameters; Animalia; Canis familiaris